Improving Aspergillus niger tannase yield by N+ ion beam implantation - Jin,Wei (2013)
This work aimed to improve tannase yield of Aspergillus niger through N+ ion beam implantation in submerged fermentation. The energy and dose of N+ ion beam implantation were investigated. The results indicated that an excellent mutant was obtained through nine successive implantations under the conditions of 10 keV and 30-40 (×2.6×10(13)) ions/cm², and its tannase yield reached 38.5 U/mL, which was about five-time higher than the original strain. The study on the genetic stability of the mutant showed that its promising performance in tannase production could be stable. The studies of metal ions and surfactants affecting tannase yield indicated that manganese ions, stannum ions, xylene and SDS contained in the culture medium had positive effects on tannase production under submerged fermentation. Magnesium ions, in particular, could enhance the tannase yield by the mutant increasing by 42%, i.e. 53.6 U/mL. Accordingly, low-energy ion implantation could be a desirable approach to improve the fungal tannase yield for its commercial application.